The Effects of The Leadership and the Supervision on the Discipline and Performance of the Employees in the Faculty of Medicine, Hasanuddin University Makassar - Ramliah Rachmat; Nurdin Brasit; Jusni Jusni (Hasanuddin Journal of Business Strategy, 2020)
This research aimed to find out the effects of the leadership and performance of the employees at the Faculty of Medicine, Hasanuddin University. The research used the quantitative approach. The population of the research included all the educational power of the state civil apparatus and all the non-permanent educational employees who worked at the Faculty of Medicine, Hasanuddin University, and had the working time of 5 (five) years. The techniques of the data collection were observation, questionnaires, and documentation. The processing and analysis of the data were conducted using the SPP (Statistical Product and Service Solution) program, version 23. The research results indicated that (1) there was a positive and significant effect of the leadership and the supervision on the discipline, (2) there was a positive and significant effect of the leadership and supervision on the employees’ performance, (3) There was a positive and significant effect of the leadership and supervision on the employees’ performance through the discipline.